Detection of galactomannan antigenemia by enzyme immunoassay in experimental invasive aspergillosis. - de Repentigny, L (1987)
A sensitive enzyme immunoassay (EIA) for galactomannan antigenemia that avoids the use of radioisotopes was devised. Three carbohydrate-rich antigenic fractions were purified from Aspergillus fumigatus 2085: a cold alkali extract (CA) from mycelium, an acetone-precipitated pyridine extract (APSK-66) from mycelium, and a methanol precipitate from culture filtrate. CA and APSK-66 were further purified by gel filtration and ion-exchange chromatography, respectively. An acid hydrolysate of CA contained only mannose and galactose, as determined by gas-liquid chromatography. Rabbit antisera were raised against conidia, mycelia, and cell walls of A. fumigatus. By indirect EIA, the best immunoglobulin G response (1/8,000) was obtained against CA in rabbits immunized intravenously with cell walls. Antigenemia was detected by indirect EIA inhibition in heat-dissociated sera of four immunosuppressed rabbits that were infected intravenously but was absent in two uninfected controls. The circulating antigen was resistant to pronase, was adsorbed onto concanavalin A, and had a molecular size of 50 to 100 kilodaltons.